การศึกษาฤทธิ์ของอนุภาคทองคำระดับนาโนเมตรต่อการเป็นพิษของเซลล์ และการแสดงออกของยีนคอลลาเจนในเซลล์ไฟโบรบลาสต์ NIH-3T3 - ชุลีปราง แดนลาดแก้ว (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
Background: Gold nanoparticles (AuNPs) have been commonly used in many cosmetic products. Commercial advertisements for AuNPs tend to promote that AuNPs aid in anti-aging, recovery of cell structure, anti-oxidant and up-regulated collagen expression. However, effects by AuNPs have been not scientifically proven. Results: In this study, it is demonstrated that AuNPs exhibit a toxic effect on NIH-3T3 fibroblast and this effect is time and dose dependent. In addition, AuNPs also show the ability to inhibit cell proliferation, down-regulate major collagen types in human skin (Col1a1, Col1a2 and Col3a1) and stimulate ROS generation. It is also found that NIH-3T3 fibroblasts response to ROS by generating NADH/NADPH which plays an important role in antioxidant mechanism. Conclusion: From the experiments, the effects of AuNPs on cytotoxicity, cell proliferation, ROS generation and expression of collagen gene depend on the amount of AuNPs as well as the time of exposure. Hence, these factors should be thoroughly considered in order to evaluate safety of AuNPs in regard to their formulations in commonly used products.